2017
DOI: 10.1073/pnas.1608488114
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation promotes TyrRS nuclear translocation to prevent oxidative damage

Abstract: Tyrosyl-tRNA synthetase (TyrRS) is well known for its essential aminoacylation function in protein synthesis. Recently, TyrRS has been shown to translocate to the nucleus and protect against DNA damage due to oxidative stress. However, the mechanism of TyrRS nuclear localization has not yet been determined. Herein, we report that TyrRS becomes highly acetylated in response to oxidative stress, which promotes nuclear translocation. Moreover, p300/ CBP-associated factor (PCAF), an acetyltransferase, and sirtuin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
52
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 44 publications
2
52
0
Order By: Relevance
“…This acetylation could activate DNA repair genes downstream of transcription factor E2F1 to protect against DNA damage in mammalian cells and zebrafish. [9] …”
Section: Introductionmentioning
confidence: 99%
“…This acetylation could activate DNA repair genes downstream of transcription factor E2F1 to protect against DNA damage in mammalian cells and zebrafish. [9] …”
Section: Introductionmentioning
confidence: 99%
“…Our study provides another evidence that PCAF and SIRT1 acting the reversible acetylation in TyrRS regulate its nuclear transport to involve with DNA damage repair, as proved in our in vivo models. 1 The present study not only reveals an unknown regulatory mechanism linking posttranslational modification to tRNA synthetases TyrRS but also enriches our knowledge of the regulatory pathway between PCAF/SIRT1 and DNA damage response. More importantly, we found that K244 acetylation of TyrRS is protective against DNA damage, suggesting a potential therapeutic opportunity to treat DNA-damage-associated diseases by targeting the K244 residue of TyrRS.…”
mentioning
confidence: 55%
“…10 Consistent with this finding, we demonstrated that resveratrol increased the acetylation level of TyrRS at K244 site in a dose-dependent manner through upregulating the expression of PCAF. 1 Together, these data suggest that under oxidative stress, PARP1 activation is due to negative feedback among SIRT1, TyrRS, and PARP1.…”
mentioning
confidence: 89%
See 2 more Smart Citations